PERANAN PERUSAHAAN DAERAH AIR MINUM SEBAGAI PENYELENGGARA KEPENTINGAN UMUM (Studi di Kabupaten Gianyar) - Handryan Giri, I Gede; R, Ibrahim; Suardita, I Ketut (Kertha Desa; Vol. 01, No. 01, Maret 2013, 2013)
Community needs for water which are increasing encourage morestrengthening economicvalue water than value and social function, these conditionscould potentially rise to a conflict of interest between sectors, between the regionsand the various parties concerned. On one side the more water management based onthe value of the economy will tend to be more in favor of capital owners and canignore social function of water resources. Based on the consideration the regionalcompanies drinking water given authority managing drinking water to provideprotection againtst the interest of the weaker economically groups by applying theprinciples of management of water resources that are able to harmonize socialfunction, environmental and economic, based on the principle of harmony and selfriliance.
Keywords: Local Drinking Water Company, Social function, Environmental and Economic, Based on the principle of harmony and self-reliance.